A Theoretical Chemistry-Based Strategy for the Rational Design of New Luminescent Lanthanide Complexes: An Approach from a Multireference Soc-Nevpt2 Method - Sanchez-Poblete, J (Royal Society of Chemistry, 2021)
Theoretical methods of the SOC-NEVPT2 type combined with a molecular fragmentation scheme have been proven to be a powerful tool that allows explaining the luminescence sensitization mechanism in Ln(iii) coordination compounds through the antenna effect. In this work, we have used this strategy to predict luminescence in a family of compounds of the Eu(R-phen)(BTA)3type whereR-phen= 5-methyl-1,10-phenanthroline (Me-phen), 5-nitro-1,10-71 phenanthroline (Nitro-phen), 4,5-diazafluoren-9-one (One-phen), or 5,6-epoxy-5,6-dihydro-1,10-72 phenanthroline (Epoxy-phen); andBTA= fluorinated β-diketone. Possible sensitization pathways were elucidated from the energy difference between the ligand-centered triplet (3T) states and the emissive excited states of the Eu(iii) fragments (Latva rules). Calculations show that the most probable mechanism occurs through the triplet state of theBTAwhich should be enriched by several parallel energy transfer pathways fromR-phensubstituents. The complexes were synthesized and structurally characterized by X-ray crystallography and various other physicochemical and spectroscopic methods to realize their optical properties and energy transfer pathways from dual antennae. Experimental results were in good agreement with the theoretical predictions, which reinforces the predictive power of the used theoretical methodology. © The Royal Society of Chemistry 2021.